Identifying farm typologies in Rwandan agriculture: A framework for improving targeted interventions - Benimana, Gilberthe Uwera; Warner, James; Mugabo, Serge (International Food Policy Research Institute, 2024)
This paper explores the broad spectrum of commercial engagement by Rwandan farmers by grouping farmers according to characteristics of the head of household, the degree of commercialization of their farms, size of livestock holdings and other factors.